Creating communities of practice as a tool for organizational learning - Miranda, Roberto Campos da Rocha (2010)
The creation of communities of practice is a common practice for organizations that adopted Knowledge Management procedures which include exchange of experiences and knowledge among collaborators. This work has as its main objective to report the experience on the creation of communities of practice within the Brazilian Institute for Information in Science and Technology (IBICT). The theoretical orientation was based on the situated cog nition approach, and the chosen methodology was based on the appreciative inquiry and on the Soft Systems Methodology (SSM). The dynamics for the creation of communities of practice in the Institute was grounded on an intensive training and on action research for the immediate implementation of the idealized communities of practice. The adopted software for the administration of communication between the participants was Moodle (Modular Object-Oriented Dynamic Learning Environment). Conceived as an open access code with an accessible language for development (PHP) it opens the possibility to align organizational requirements to the software’s environment and presents a group of modules which allows the participant’s evaluation. As result of this experience communities of practice were created in the Institute and are fully operational, each with a group of 5 people.